PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP KONSEP DIRI - Rosalina, Lutfah; Budiono, Arifin Nur; Wahyuni, Wahyuni (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This research was conducted to find out the extent of the influence of the intensity of the use of gadgets on the self-concept of class XI SMA Plus Al-Hasan Panti. The research method used is quantitative method and simple correlation. The participants were taken randomly using simple random sampling. This research was conducted by distributing a questionnaire to a predetermined sample. Based on the statistical test using the Pearson product-moment test, the r-value was 0.317 compared to the r table, the results obtained were 0.213. Further, the t-value was 3,064 compared to the t table, the results were 1,989, which means Ha was accepted and HO was rejected. Therefore, the gadget has a positive correlation with the students’ self-concept. Keywords: gadgets, self concept